Participatory democracy and urban governance in France: Are they still utopian views' - Olivier Thomas (European Regional Science Association (ERSA), 2003)
This paper aims at questionning the relevance of the current use of the notion of governance in urban economics. As a starting point, the lack of an appropriate background ( due to the kind of participating actors, the way they are organized and deal with common problems), will be supposed to shackle practical experiences which are in relation to urban governance. Consequently, these experiences could not be easily spreaded, contrary to the main theoerical belief. Our empirical field will concern the current government of French cities during the last two decades. Thus, contrary to the prevailing trend of the literature, the reasons why urban governement of French cities would not entail an increasing level of urban governance and participative democracy will be developed. In order to test our main assumption, terminological borrowed words in relation to governance, municipal and metropolitan institutionnal constraints, and finally weaknesses of citizens associations will be successively taken into account.
Keywords: 330